2020
DOI: 10.1016/j.anbehav.2020.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Information use in foraging flocks of songbirds: no evidence for social transmission of patch quality

Abstract: Animals use behavioural cues from others to make decisions in a variety of contexts. There is growing evidence, from a range of taxa, that information about the locations of food patches can spread through a population via social connections. However, it is not known whether information about the quality of potential food sources transmits similarly. We studied foraging behaviour in a population of wild songbirds with known social associations, and tested whether flock members use social information about the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 48 publications
0
14
1
Order By: Relevance
“…We inferred the social position of individuals by creating a network based on the foraging associations of PIT-tagged birds at feeders. While information about the social behavior of birds is restricted to a foraging context at artificial feeders and thus may not represent their natural association patterns, previous work on tits (Paridae) has demonstrated that foraging associations are meaningful in predicting processes in other contexts such as the discovery of novel food patches ( Aplin et al 2012 ; Hillemann et al 2020 ), the spatial breeding arrangement ( Firth and Sheldon 2016 ; Beck et al 2020 ) and mating patterns ( Beck et al 2020 ). We used data from the two months before the start of breeding (from 1 February until 13 March 2018) to create a social network.…”
Section: Methodsmentioning
confidence: 99%
“…We inferred the social position of individuals by creating a network based on the foraging associations of PIT-tagged birds at feeders. While information about the social behavior of birds is restricted to a foraging context at artificial feeders and thus may not represent their natural association patterns, previous work on tits (Paridae) has demonstrated that foraging associations are meaningful in predicting processes in other contexts such as the discovery of novel food patches ( Aplin et al 2012 ; Hillemann et al 2020 ), the spatial breeding arrangement ( Firth and Sheldon 2016 ; Beck et al 2020 ) and mating patterns ( Beck et al 2020 ). We used data from the two months before the start of breeding (from 1 February until 13 March 2018) to create a social network.…”
Section: Methodsmentioning
confidence: 99%
“…all individuals that had previously arrived at the patch). Following Hillemann et al [47], we compared these observed patterns to a null model which simulated individuals arriving at the feeder in random order, generated by randomly selecting k individuals from the local network. This null model assumes social learning plays no role in feeder discovery.…”
Section: (Iii) Model Simulationsmentioning
confidence: 99%
“…Thus, sociality can only evolve where the benefits outweigh the costs (Krause and Ruxton 2002; Silk 2007; Silk et al 2014). For example, communal foraging during the non-breeding period can facilitate information transfer between individuals (Aplin et al 2012; Hillemann et al 2020) and reduce predation risk (Cresswell and Quinn 2011). But during the breeding season these benefits also incur costs associated with competition for resources, mates (Le Galliard et al 2005; Grant and Grant 2019; Kurvers 2020; but also see Lea et al 2010) and offspring paternity (Birkhead and Biggins 1987; Forstmeier et al 2011; Mayer and Pasinelli 2013).…”
Section: Introductionmentioning
confidence: 99%